Acute interstitial nephritis observed with three different triggering agents. Issue 3 (18th March 2022) - Nobakht, Niloofar; Hanna, Ramy M.; Kamgar, Mohammad; Sinclair, John; Simon, Lewis; Emami, Sina; Sisk, Anthony; Rastogi, Anjay
Abstract: A 70‐year‐old female patient developed acute interstitial nephritis (AIN) after treatment with non‐steroidal anti‐inflammatory drugs (NSAIDs), proton pump inhibitors (PPI), and Bromhexine. Renal biopsy confirmed the diagnosis, and the patient was treated with oral prednisone. Careful attention to timing of acute kidney injury (AKI) is crucial to diagnosing AIN. Abstract : Several drugs can cause allergic interstitial nephritis (AIN) including over the counter agents. Bromhexine an over the counter cough remedies can be associated with AIN. The timing of treatment initiation with steroid is critical to decrease risk of fibrosis and future chronic kidney disease and loss of GFR.